Optimization of a Miniaturized and Rapid Sample Preparation Method for HPLC Quantification of Flavonoids in Honey by Response Surface Methodology - Stavrou, Konstantina; Christou, Atalanti; Goulas, Vlasios (My University, 2025)
In this article, the authors were incorrectly listed as Konstantina Stavrou and Atalanti Christou Vlasios Goulas. The correct authorship should read: Konstantina Stavrou, Atalanti Christou, and Vlasios Goulas. The original article has been corrected.